(untitled) (Faridpur Medical College Journal, 2017)
Iron deficiency anaemia and febrile seizures are two common diseases in children worldwide as well as in developing country. A prospective case-control study was carried out in the Department of Paediatrics, Faridpur Medical College Hospital. The study was done during the period from January’2015 to September’2015 with 50 children with first simple febrile seizure as cases and other 50 controls. There were no significant differences in terms of ESR, WBC, platelets, RBC, MCHC, and TIBC levels between the cases and the control group. HB, HCT, MCH, mean serum ferritin and serum iron, were significantly low in the febrile convulsion group as compared to control group. Faridpur Med. Coll. J. Jul 2016;11(2): 44-46